Dialogue and Difference - Waller, M. author. aut Link
XXXI, 259 p.
Keywords: Calling for inclusion and dialogue, these essays by an international group of feminist scholars and activists stress the need to put into relation seemingly discrepant approaches to reality and to scholarship in order to build coalitions across the usual North/South and East/West divides. This diverse group of authors, who spent fourteen weeks working collaboratively, dispense with unity and seek instead to use dialogue and difference in their production of knowledge about effective political action. The dialogues materialized here among women's movements that have emerged within different contexts and cosmologies take feminisms' challenges to contemporary corporate globalization in new empirical and theoretical directions.